2016
DOI: 10.1007/s11356-015-5970-9
|View full text |Cite
|
Sign up to set email alerts
|

Photosynthetic and growth responses of Schima superba seedlings to sulfuric and nitric acid depositions

Abstract: A continuing rise in acid deposition can cause forest degradation. In China, acid deposition has converted gradually from sulfuric acid deposition (SAD) to nitric acid deposition (NAD). However, the differing responses of photosynthesis and growth to depositions of sulfuric vs. nitric acid have not been well studied. In this study, 1-year-old seedlings of Schima superba, a dominant species in subtropical forests, were treated with two types of acid deposition SO4 (2-)/NO3 (-) ratios (8:1 and 0.7:1) with two ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 44 publications
3
9
0
Order By: Relevance
“…Inconsistent with the earlier findings that increased N application increases the chlorophyll content (Granath et al, 2009b ; Yao et al, 2016 ; Zhang et al, 2016 ), we found that chlorophyll content was not significantly affected by N deposition in Moso bamboo. A similar lack of response was also observed in R. squarrosus (Arróniz-Crespo et al, 2008 ).…”
Section: Discussionsupporting
confidence: 87%
“…Inconsistent with the earlier findings that increased N application increases the chlorophyll content (Granath et al, 2009b ; Yao et al, 2016 ; Zhang et al, 2016 ), we found that chlorophyll content was not significantly affected by N deposition in Moso bamboo. A similar lack of response was also observed in R. squarrosus (Arróniz-Crespo et al, 2008 ).…”
Section: Discussionsupporting
confidence: 87%
“…The plant biomass accumulation also showed a similar trend consistent with previous results [ 27 , 28 ]. Direct acid spraying may damage the key components of the plant [ 3 ], resulting in the destruction of physiological functions (such as low P n and chlorophyll content) and then slow growth, which was consistent with previous findings [ 29 , 30 , 31 ].…”
Section: Discussionsupporting
confidence: 90%
“…High net photosynthetic rate in soil application treatments further explained better performance in growth and biomass accumulation [ 24 ]. However, the biomass improvement only appeared when treated with a low pH acid rain (the total biomasses of SL4.5 and NL4.5 were 316.30 ± 2.08 g and 309.10 ± 14.88 g), an observation which was reported in previous studies [ 3 , 24 ].…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations